Gender-biased neologisms: the case of man-X - Océane Foubert; Maarten Lemmens (Lexis: Journal in English Lexicology)
This article presents a semantic and frequency-based diffusion analysis of one specific type of gendered coinages that we will refer to as “man-neologisms” such as man bun, mancation (man + vacation) or manspread. Our study (based on Foubert [2018]) reveals that man in these coinages only rarely carries a generic meaning (referring to human beings in general, as in man is mortal) but mostly have a gender-specific meaning (“of, or related to, men”). Our analysis of the meanings of these man-specific neologisms shows that they are gender specific and mainly concern domains which are typically associated with women. Moreover, our analysis reveals four motivations behind the coinages of man-neologisms: (i) the reappropriation of domains which are typically associated with women, as in man purse (a purse for men), (ii) the reinforcement of differences, such as man cave (a room for men only), (iii) the confirmation of stereotypes, as in man science (a branch of knowledge available to men only), (iv) and naming undesirable male behaviours, mainly in an attempt to change them, such as mansplain (man + explain; men explaining things to women in a condescending way). The diffusion analysis observing the frequency of occurrences of man-neologisms reveals that neologisms aiming at the reappropriation of domains and particularly those naming undesirable male behaviours are less numerous in the list of coinages themselves, but more inclined to be diffused, contrary to neologisms reinforcing differences and confirming stereotypes.